2004
DOI: 10.1007/s11746-004-1027-z
|View full text |Cite
|
Sign up to set email alerts
|

Molecular mapping and identification of soybean fatty acid modifier quantitative trait loci

Abstract: Altering FA content in soybean [Glycine max (L.) Merr.] oil for improved functionality is a research goal of many soybean breeders. Several of the genes that alter palmitic, stearic, oleic, linoleic, and linolenic acids are modifier genes with small effects, causing these FA traits to act as quantitative traits. The objective of this study was to identify modifier FA quantitative trait loci (QTL) in soybean. A recombinant inbred line population was created from two prominent ancestors of currently available U.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
37
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 54 publications
(44 citation statements)
references
References 21 publications
7
37
0
Order By: Relevance
“…Previous studies on fatty acids were mainly aimed at improving the quality of soybean oil for human consumption, i.e., decreasing saturated and polyunsaturated fatty acids and increasing monounsaturated acid (Erickson et al 1988;Nickell et al 1991;Li et al 2002;Oliva et al 2006;Panthee et al 2006;Primomo et al 2002;Hyten et al 2004b;Cardinal et al 2007). Soybean lines with reduced palmitic acid or stearic acid content have been developed through mutagenesis, recurrent selection and hybridization (Erickson et al 1988;Bubeck et al 1989;Wilcox and Cavins 1990;Burton et al 1994).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies on fatty acids were mainly aimed at improving the quality of soybean oil for human consumption, i.e., decreasing saturated and polyunsaturated fatty acids and increasing monounsaturated acid (Erickson et al 1988;Nickell et al 1991;Li et al 2002;Oliva et al 2006;Panthee et al 2006;Primomo et al 2002;Hyten et al 2004b;Cardinal et al 2007). Soybean lines with reduced palmitic acid or stearic acid content have been developed through mutagenesis, recurrent selection and hybridization (Erickson et al 1988;Bubeck et al 1989;Wilcox and Cavins 1990;Burton et al 1994).…”
Section: Discussionmentioning
confidence: 99%
“…These QTL were associated with simple sequence repeat (SSR) markers Satt684 and Satt175, respectively, and accounted for 51% of the total phenotypic variation in the F 2 population and 43% of the variation in the F 2:3 population. Hyten et al (2004b) detected 12 QTL on six linkage groups for the fatty acids in an F 6 -derived recombinant inbred line (RIL) population and identified a single marker interval on linkage group L associated with palmitic, oleic, linoleic and linolenic acids. Panthee et al (2006) reported that the SSR marker Satt537 on linkage group D1b was associated with palmitic acid; and Satt168 and Satt429 on linkage groups B2 and J, respectively, were associated with stearic acid.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The significant effects of this QTL were further confirmed by group comparison (Table 3). Hyten et al (2004b) reported a QTL with R 2 = 8.1 % at the position of 11.4 cM with the closest marker Satt269 on linkage group F (Chr 13) on the integrated soybean genetic map (Song et al 2004). In their study, the QTL resulted in only a small change in linolenic acid concentration (1.9 g/kg), showing the smallest effect among all three QTLs for linolenic acid.…”
Section: Comparison Of Qtls Detected In Different Studiesmentioning
confidence: 95%
“…Quantitative trait locus (QTL) analysis of oil content and fatty acids in soybean has been reported (Diers and Shoemaker 1992;Li et al 2002;Fasoula et al 2004;Hyten et al 2004a, b). Hyten et al (2004b) detected 12 QTLs on six linkage groups for the fatty acids in an F 6 -derived recombinant inbred line (RIL) population and identified a single marker interval on linkage group L [chromosome (Chr) 19] associated with palmitic, oleic, linoleic and linolenic acids. Panthee et al (2006) mapped four QTLs on linkage groups E (Chr 15) and G (Chr 18) for oleic, linoleic and linolenic acids in an F 6 -derived RIL population.…”
Section: Introductionmentioning
confidence: 99%